Intraspecies variability of fatty acid content and composition of a cosmopolitan benthic invertebrate, Gammarus lacustris. Issue 3 (3rd July 2018) - Makhutova, Olesia N.; Shulepina, Svetlana P.; Sharapova, Tatyana A.; Kolmakova, Anzhelika A.; Glushchenko, Larisa A.; Kravchuk, Elena S.; Gladyshev, Michail I.
ABSTRACT: Aquatic invertebrates are valuable dietary sources of essential polyunsaturated fatty acids, eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3), for fish. Phylogeny, diet, and various ecological factors affect the fatty acid composition of aquatic invertebrates. We focused our study on the effect of ecological factors to a cosmopolitan species inhabiting lakes that differed in salinity, temperature, and presence/absence of predators (fish). To avoid the effect of phylogeny, which strongly influences the fatty acid composition of animals, we studied several populations of one cosmopolitan benthic species, Gammarus lacustris Sars. We found that differences in fatty acid percentages of G. lacustris were mainly affected by differences in their diets. Some populations preferred dinoflagellates, cryptophytes, green algae/cyanobacteria, and bacteria; other populations selected diatoms; and still other populations consumed zooplankton or allochthonous (terrestrial) organic matter. The salinity and presence/absence of fish affected the contents of EPA and DHA in G. lacustris . Populations from saline and fishless lakes had significantly higher contents of EPA and DHA. Thus, stocking of fishless lakes dominated by G. lacustris with fish could lead to a decrease in EPA and DHA contents in the gammarids. We propose that some saline and fishless lakes could be used as a source of gammarids for aquaculture fish feeding.